A rare case of an anterior and posterior synovial chondromatosis of the knee joint with postoperative common peroneal nerve neuropraxia: An overview of surgical approach - Harish mahesan; Parthiban jeganathan; Suresh Perumal; Arumugam Sivaraman (Journal of Orthopaedic Reports)
Synovial chondromatosis (SCM) is a rare condition characterized by cartilaginous metaplastic of synovium that ossify and gets extruded into the joint space as loose bodies. Giant synovial chondromatosis arises from multiple small synovial chondromas or from a single large chondroma, which roughly measure from 5cm to 20cm in size. The case report highlights the surgical approach and subsequent complications in managing of a 17yrs old patient with large synovial chondroma posteriorly along with multiple small chondromas on the anterior aspect of the knee, and the posterior chondroma was found in close proximity to the popliteal vessel and common peroneal nerve.